1984
DOI: 10.1152/ajpgi.1984.246.5.g563
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic nervous control of cAMP-mediated amylase secretion in the rat pancreas

Abstract: In this study of nervous control of exocrine secretion, electrical field stimulation (FS) evoked a marked, tetrodotoxin-sensitive increase in the amylase output from in vitro segments of rat pancreas. Blockade of the large cholinergic component of the response by atropine revealed a smaller noncholinergic nerve-mediated secretion. This noncholinergic secretion was unaffected by phentolamine but abolished by propranolol, as were the secretory responses to norepinephrine and other beta-adrenergic agonists. FS al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
2

Year Published

1984
1984
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 0 publications
6
34
2
Order By: Relevance
“…These observations corroborate several other findings (Adeghate & Donàth, 1990, 1991. In addition to the classical neurotransmitters (ACh and NA) which innervate the pancreas (Lenninger, 1974;Pearson et al 1984) it is now well established that the pancreas is also innervated by peptidergic nerves which release several neuropeptides including CCK, substance P, neuropeptide Y, vasoactive intestinal polypeptide and several others (Adeghate & Donàth, 1990;Holst, 1993;Adeghate et al 1997). The results of this study have confirmed the presence of CCK-immunopositive nerves in the endocrine pancreas and around blood vessels of normal and diabetic animals.…”
Section: Immunohistochemistrysupporting
confidence: 86%
See 1 more Smart Citation
“…These observations corroborate several other findings (Adeghate & Donàth, 1990, 1991. In addition to the classical neurotransmitters (ACh and NA) which innervate the pancreas (Lenninger, 1974;Pearson et al 1984) it is now well established that the pancreas is also innervated by peptidergic nerves which release several neuropeptides including CCK, substance P, neuropeptide Y, vasoactive intestinal polypeptide and several others (Adeghate & Donàth, 1990;Holst, 1993;Adeghate et al 1997). The results of this study have confirmed the presence of CCK-immunopositive nerves in the endocrine pancreas and around blood vessels of normal and diabetic animals.…”
Section: Immunohistochemistrysupporting
confidence: 86%
“…The secretion of pancreatic juice is controlled mainly by the autonomic nervous system (Lenninger, 1974;Pearson et al 1984) and by the two naturally occurring gut hormones, secretin and cholecystokinin (Chey, 1993). More recently, other substances including the islet hormones, vasoactive intestinal polypeptide (VIP), phorbol esters, nitric oxide, histamine and the growth hormones have been implicated in the regulation of exocrine pancreatic secretion (Pearson et al 1982;Singh, 1985a;Nishizuka, 1988;Owyang, 1993;Williams & Goldfine, 1993;Lajas et al 1996;Singh et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Experiments were performed according to the method of Pearson et al (1984), with minor modifications. were killed by a blow to the head and the pancreas was quickly removed and placed in a modified Krebs-Henseleit solution of the following composition (mM): NaCl 103, KCI 4.7, CaCl2 2.56, MgCl2 1.13, NaHCO3 25, NaH2PO4 1.15, D-glucose 2.8, sodium pyruvate 4.9, sodium fumarate 2.7, and sodium glutamate 4.9.…”
Section: In Vitro Experimentsmentioning
confidence: 99%
“…Interestingly, in the same series of experiments atropine completely blocked the secretory response evoked by ACh and markedly reduced the amylase output elicited by EFS. The failure of atropine to abolish the effect of EFS completely is not strange, since in the rat pancreas part of the nerve-mediated secretory response is due to a sympathetic component (Pearson et al 1984). Furthermore, it is unlikely that secretin is acting to inhibit the release of ACh during EFS, since the gut hormone can also attenuate the secretagogue effect of exogenous application of ACh.…”
Section: Discussionmentioning
confidence: 99%
“…The technique of electrical field stimulation has been shown previously to be a useful and effective physiological tool for activating intrinsic nerves in the in vitro pancreas to study the effect of endogenous neurotransmitters on pancreatic secretion (Davison et al 1980;Pearson et al 1984). This present study has also shown that stimulation of intrinsic secretomotor nerves in the isolated rat pancreas can result in marked increases in amylase secretion, which are associated with an elevation in cytosolic free Ca2" concentration, radiolabelled Ca2" influx and a net efflux of Mg2".…”
Section: Discussionmentioning
confidence: 99%